First zoeal stage of Macrocoeloma subparallelum (Stimpson, 1860 ( Decapoda: Brachyura: Majoidea described from laboratory hatched material - Colavite, Jessica [UNESP]; Lopez, Regulo; Hernandez, Jesus; Bolanos, Juan; Santana, William [UNESP] (Soc Brasileira Carcinologia, 2016)
The morphology of the first zoeal stage of the decorator crab Macrocoeloma subparallelum (Stimpson, 1860) from Cuba is described and compared with the available descriptions for the genus. Among Macrocoeloma Miers, 1879 species, the first zoea of M. subparallelum can be differentiated only by the number of aesthetascs and setae of the antennule (4 and 2, respectively). Recently, Macrocoeloma has been placed as an incertae sedis genus in Majoidea, closely allied to other Epialtidae and Pisinae members. The distinct spine in the distal segment of the endopod of the first maxilliped in the zoeal stages of Macrocoeloma is similar to what we observe in other Epialtidae genera, a character that supports the recent phylogenetic findings.
Keywords: Cuba; Pisinae; Epialtidae; Mithracidae; larval development